THE EFFECTIVENESS OF GOVERNMENT REGULATION (PP) NO. 60 OF 2008 ON GOVERNMENT INTERNAL CONTROL SYSTEM IN NORTH SUMATERA - Eka Nurmala Sari; Maya Sari; Abdul Mughni Fahrizan Sitompul (Journal of Islamic, Social, Economics and Development, 2023)
This study aims to see how the effectiveness of the internal control system of government , especially in local governance North Sumatera in Indonesia, The research method is the research method with explanatory approach (explanatory research), while the type of research is descriptive. Population in this research is All Regional Government in North Sumatera Province. The target population is the district and city governments in North Sumatra. Furthermore, the unit of analysis is the Regional Government consisting of 33 (thirty three) District and City Governments in North Sumatra. In this study, the type of data is qualitative and quantitative data that consist of questionnaires, interviews and documentation data. Sources of data are primary data and secondary data. Qualitative or primary data are obtained from respondents with data collection techniques, they are: questionnaires and documentation. Primary data is collected by spreading the questionnaire which needs to be tested first with the consideration that the seriousness of respondents in answering the questions is very important in this study. The technique analysis is descriptive analysis. It is by explaining in detail of the problems that occursThe results showed that the internal control system of government on governance in North Sumatra is still inadequate can be proven by the physical control of assets which not inadequate, is still inadequate commitment to competence, a good working relationship with the relevant government, risk analysis, and recording and documentation, only indicator that is conducive leadership, the role of internal control apparatus, separation of duties and monitoring have adequate conditions while the rest goes into the category quite adequate.